One must imagine Sisyphus happy: Integrative taxonomic characterization of 22 new Ceroptres species (Hymenoptera: Cynipidae: Ceroptresini) - Nastasi, Louis F.; Smith, Cecil N.; Davis, Charles K.; Ward, Anna K.g.; Brown, Guerin; Zhang, Y. Miles; Rollins, Shannon; Friesen, Chris; Tribull, Carly M.; Forbes, Andrew A.; Deans, Andrew R. (Zootaxa, 2024)
We describe new species in the genus Ceroptres Hartig, 1840 (Hymenoptera: Cynipidae: Ceroptresini) represented by voucher material sequenced by Ward et al. (2024). We describe 22 new species, all authored by Nastasi, Smith, & Davis: C. anansii sp. nov., C. anzui sp. nov., C. bruti sp. nov., C. curupira sp. nov., C. daleki sp. nov., C. dandoi sp. nov., C. demerzelae sp. nov., C. iktomii sp. nov., C. jabbai sp. nov., C. jarethi sp. nov., C. lokii sp. nov., C. lupini sp. nov., C. mallowi sp. nov., C. promethei sp. nov., C. sandiegoae sp. nov., C. selinae sp. nov., C. soloi sp. nov., C. songae sp. nov., C. swiperi sp. nov., C. thrymi sp. nov., C. tikoloshei sp. nov., and C. zorroi sp. nov. After our taxonomic treatment, the genus Ceroptres includes 43 species, all but three of which are known from North America. Among our new species are two reared from cecidomyiid midge galls, an association previously recorded but without valid taxonomic association. We provide new records for two additional previously described species; we record C. ensiger (Walsh, 1864) from Pennsylvania and confirm characters for the male, and we record C. lanigerae Ashmead, 1885 from Texas. We also examined several putative species corresponding to either C. cornigera Melika & Buss, 2002 and/or C. frondosae Ashmead, 1896, which we regard as a species complex that requires elucidation in future studies. To enable further studies on Ceroptres, we provide an updated key to North American females. Overall, we find that species of Ceroptres are host specialists associated with a single host gall species or several galls that are phylogenetically or ecologically related. We suggest that there are many North American species of Ceroptres, possibly hundreds, still awaiting collection and characterization.